THE INFLUENCE OF THE ROLE OF SCHOOL, PARENTS AND COMMUNITIES ON THE QUALITY OF EDUCATION IN SMP NEGERI 2 PANGURURAN SAMOSIR REGENCY IN ACADEMIC YEAR 2018/2019 - enny juliana pelita naibaho (English Language Teaching Prima Journal (ELT), 2019)
The purpose of the study was to analyze the role of schools, the role of parents in the role of the community and analyze the role of schools, parents and the community on the quality of school education in Pangururan 2 Public Middle School, Samosir Regency. The research method used multiple linear regression analysis. The results of the study (1) the value of tcount for the variable learning planning teacher ability 19.578 is greater than the ttable 0.1918 at the significance of 0.05 and the sig value of 0.00 is smaller than alpha 0.05. Based on the results obtained, Ho is rejected and H1 is accepted. The role of schools has an effect of 79.16% on the quality of education in Pangururan 2 Public Middle School. (2) Value of tcount for parent role variable 11, 258 greater than t table 0.1918 and sig value 0.000 smaller than alpha 0.05. Based on the results obtained, Ho is rejected and H1 is accepted. The role of parents affects 28.2% of the quality of education in Pangururan 2 Public Middle School (3). The value of tcount for the variable community role 6,680 is greater than t table 0,1918 and the value of sig 0,000 is smaller than alpha 0.05. Based on the results obtained, Ho is rejected and H1 is accepted. The role of the community has an effect of 30.6% on the quality of education in Pangururan 2 Public Middle School. (4). The value of Fcount 173.478 is greater than Ftable 2.70 or the value of sig 0.000 is smaller than alpha 0.05. Based on the results obtained, Ho is rejected and H1 is accepted. The role of schools, parents and the community has an effect of 80.5% on the quality of education in Pangururan 2 Public Middle School